2022
DOI: 10.3389/fmicb.2022.842372
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-Mediated Assembly of Plant-Beneficial Bacteria to Alleviate Fusarium Wilt in Pseudostellaria heterophylla

Abstract: Fusarium wilt (FW) is a primary replant disease that affects Pseudostellaria heterophylla (Taizishen) and is caused by Fusarium oxysporum, which occurs widely in China under the continuous monocropping regime. However, the ternary interactions among the soil microbiota, P. heterophylla, and F. oxysporum remain unknown. We investigated the potential interaction relationship by which the pathogen-mediated P. heterophylla regulates the soil and the tuberous root microbiota via high-throughput sequencing. Plant–pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…One study showed that in the rhizosphere of P. heterophylla, the presence of F. oxysporum promotes the growth of P. poae and also is responsible for attracting it [53]. This bacterium has been noticed to be beneficial in the conversion of phosphorous to make it available for plant uptake and in some cases also for nitrogen [54]. In enabling the uptake of nutrients by breaking them down this bacterium is known to enhance plant height [55].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that in the rhizosphere of P. heterophylla, the presence of F. oxysporum promotes the growth of P. poae and also is responsible for attracting it [53]. This bacterium has been noticed to be beneficial in the conversion of phosphorous to make it available for plant uptake and in some cases also for nitrogen [54]. In enabling the uptake of nutrients by breaking them down this bacterium is known to enhance plant height [55].…”
Section: Discussionmentioning
confidence: 99%
“…P . palleroniana strain B-BH16-1 was cultured in LB medium and incubated in a shaker at 180 rpm at 28 °C in darkness for 48 h. The bacterial body was collected for DNA extraction as described previously [ 47 ]. The V3V4 fragment of rRNA sequences was amplified with universal primers 338F (5′-ACTCCTACGGGAGGCAGCAG-3’) and 806R (5′-GGACTACHVGGGTWTCTAAT-3’) [ 48 ].…”
Section: Methodsmentioning
confidence: 99%